Cotton and Market: Cotton Exportation in the Republic of New Granada and the Internal Market of Spain during the XVIII Century (Papeles, 2019)
This article studies the causes of the detriment of cotton fiber exports from New Granada to the Spanish Peninsula during the last quarter of the 18th century. The hypothesis that we verified, by econometric and qualitative methods, is that theweakness of the Spanish internal market was the fundamental factor that explains this decrease in cotton exports from New Granada. This required a theoretical reflection on the causes of economic growth in a pre-industrial society and the importance.
Keywords: Cotton; Market; Exportation; Republic of New Granada; Spain